Physiological Responses to Acute Cycling With Blood Flow Restriction - Kilgas, Matthew A.; Yoon, Tejin; McDaniel, John; Phillips, Kevin C.; Elmer, Steven J. (Frontiers in Physiology, 2022)
Aerobic exercise with blood flow restriction (BFR) increases both muscle function and aerobic capacity. Despite these benefits, there are no standardized guidelines for the application of pressure for aerobic exercise with BFR. We compared blood flow, tissue perfusion, and neuromuscular function to acute cycling with and without BFR. Ten participants completed four intermittent cycling (6x2min) conditions including: low-load cycling (LL), low-load cycling with moderate BFR (BFR60), low-load cycling with high BFR (BFR80), and high-load cycling (HL). Limb blood flow, tissue perfusion, VO2, ventilation, heart rate, perceived effort, and pain during exercise, as well as pre- to post-exercise changes in blood lactate and knee extensor muscular function were assessed. Cycling with BFR60 and BFR80 caused a 33 and 50% reduction in blood flow and a 5 and 15% reduction in tissue perfusion, respectively, compared to LL (all P < 0.05). BFR60 resulted in lower cardiorespiratory, metabolic, and perceptual responses compared to HL (all P < 0.05), whereas BFR80 resulted in similar heart rates and ratings of perceived exertion to HL (both P > 0.05). Cycling with BFR60 and BFR80 resulted in a 18 and 40% post-exercise reduction in neuromuscular torque, respectively (both P < 0.05). Knee extensor torque in the BFR80 condition was compromised through a combination of peripheral and central mechanisms. Intermittent cycling with BFR at 60% and 80% of limb occlusion pressure increased metabolic stress, and decreased blood flow and neuromuscular function. However, only BFR60 did so without causing excessive discomfort and cardiorespiratory strain. Therefore, cycling with BFR at this pressure may serve as an alternative to high-intensity exercise.